2002
DOI: 10.1002/prep.200290000
|View full text |Cite
|
Sign up to set email alerts
|

2,2‐Dinitro‐1,3‐Bis‐Nitrooxy‐Propane (NPN): A New Energetic Plasticizer

Abstract: A new energetic plasticizer, 2,2‐dinitro‐1,3‐bis‐nitrooxy‐propane (NPN), has been characterized. Its high oxygen balance, +12.5%, and low glass transition temperature, −81.5 °C (midpoint), makes it very attractive as an energetic plasticizer in solid propellants. The ability of NPN to lower the glass transition temperature and viscosity of uncured PolyNIMMO has been studied and compared to other energetic plasticizers, such as BDNPA/F and butyl‐NENA. NPN has a similar plasticizing effect as butyl‐NENA, both on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 7 publications
1
33
0
Order By: Relevance
“…The influence of nitro group on the decomposition of nitrate ester was also observed in the study on the thermal stability of 2,2-dinitro-1,3-bis-nitroxy-propane (III) energetic plasticizer [13]. It was confirmed that this plasticizer could not be available in propellant formulation because it decomposed in 2 days at 65 8C.…”
Section: Introductionmentioning
confidence: 67%
“…The influence of nitro group on the decomposition of nitrate ester was also observed in the study on the thermal stability of 2,2-dinitro-1,3-bis-nitroxy-propane (III) energetic plasticizer [13]. It was confirmed that this plasticizer could not be available in propellant formulation because it decomposed in 2 days at 65 8C.…”
Section: Introductionmentioning
confidence: 67%
“…Extensive studies on the formation of energetic materials have been carried out to formulate high-energy propellants and explosives [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Crystalline energeticmaterials are composed of carbon structures.…”
Section: Physicochemical Properties Of Crystalline Materialsmentioning
confidence: 99%
“…The introduction of bu-NENA based gun propellant formulations would allow a better and mechanically improved, energetically enhanced, and less sensitive gun propellant [10][11][12][13][14]. There are some studies concerning their synthesis [15][16][17] and their explosive properties as insensitive energetic explosives [18][19][20]. Since its synthesis, alkyl-NENA has been at the center of intense research.…”
Section: Introductionmentioning
confidence: 99%